Effect of Grouping, Segmentation, and Vestibular Stimulation on the Autokinetic Effect. (January 2018) - Ramachandran, Vilayanur S.; Chunharas, Chaipat; Croft, Rachel; Batal, Nader
We report some new observations on what could be regarded as the world's simplest visual illusion—the autokinetic effect. When a single dim spot of light is viewed in a completely dark room, it moves vividly in random directions. During steady fixation, perhaps subtle eye movements cause the image to move and a failure to correct for this using eye movement command signals leads to motion perception. This is especially true because eye muscle fatigue can lead to miscalibration. However, if two dots are shown, they often move independently in different directions, which negate the eye movement theory. In addition, two lines defining a single cross sometimes uncouple and slide past each other and the fragments composing a hidden object move independently until they click in place and the whole object is perceived—implying that the illusion occurs relatively late in visual processing. Finally, the effect is modulated by vestibular stimulation; anchoring your sense of self may be a prerequisite for binding features into coherent objects.